A study on knowledge, attitude and practices regarding antenatal care among pregnant women attending antenatal clinic at a tertiary care hospital - Kaur, Rajvir; Taneja, Poonam; Nandal, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The maternal health level of Indian women was noticed to be inferior as compared to other developed countries. Antenatal care is the clinical assessment of both mother and foetus, during the period of pregnancy. Safe motherhood by providing good antenatal care (ANC) is very crucial to reduce maternal mortality ratio and infant mortality rate and to achieve millennium development goals. The objectives of this study aimed to assess the level of knowledge, attitude, and practice on ANC among pregnant women attending the antenatal clinic and their association with several sociodemographic factors. Methods: A cross-sectional study was undertaken among 200 pregnant women in their 3rd trimester attending the OPD in a Tertiary Care Hospital of Gurugram, Haryana. Predesigned questionnaire was used for collecting data by interview after obtaining informed consent. Results: This study revealed that about 55% women had adequate knowledge regarding ANC. It was found that almost all the variables such as age, parity, level of education, occupation and type of family had a significant association with awareness about ANC. 90% women were having a positive attitude towards ANC. Around 70%, women were practicing this adequately. Conclusions: These results can be used to design a Health Intervention Program targeting to upgrade the maternal health practices and ultimately progress the health status of the women.